2017
DOI: 10.1136/annrheumdis-2017-211287
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in theNCF1gene leading to reduced oxidative burst is associated with systemic lupus erythematosus

Abstract: These results clearly demonstrate that a genetically controlled reduced production of ROS increases the risk of developing SLE and confirm the hypothesis that ROS regulate chronic autoimmune inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
101
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 35 publications
8
101
1
Order By: Relevance
“…It causes joint pain and degradation, and, if left untreated, can lead to cardiovascular disease and other comorbidities that result in disability and decreased quality of life. RA is in part dependent on genetics; among the genes that are reported to contribute to the development of RA are the major histocompatibility complex (MHC) class II region, protein tyrosine phosphatase N22, and neutrophil cytosolic factor 1 (NCF‐1) . NCF‐1 has an essential role in the NADPH oxidase 2 (NOX‐2) complex, which in turn has an important role in the defense against pathogens through the production of reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…It causes joint pain and degradation, and, if left untreated, can lead to cardiovascular disease and other comorbidities that result in disability and decreased quality of life. RA is in part dependent on genetics; among the genes that are reported to contribute to the development of RA are the major histocompatibility complex (MHC) class II region, protein tyrosine phosphatase N22, and neutrophil cytosolic factor 1 (NCF‐1) . NCF‐1 has an essential role in the NADPH oxidase 2 (NOX‐2) complex, which in turn has an important role in the defense against pathogens through the production of reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…The importance of ROS in the regulation of inflammation also gains support from our earlier studies in which we through positional cloning of a disease linked genetic polymorphism, have identified Ncf1 (encoding for the p47 phox subunit of the NADPHoxidase complex) as a disease-associated gene [19] and the molecular basis being linked to a compromised ROS production [20]. Similarly, polymorphism of Ncf1 plays a role in human autoimmune diseases [21,22], and in animal models, it has been shown to be of importance for disease severity of arthritis, psoriasis, colitis, and lupus, reviewed in [14,23]. It is apparent from both pharmacological and genetic deletion studies, that FPRs have multiple roles in diseases conditions associated with a dysregulated inflammation.…”
Section: Introductionmentioning
confidence: 85%
“…We previously showed that a single nucleotide polymorphism in Ncf1, resulting in loss-offunction amino acid substitution, led to an increased risk of developing arthritis [3,4]. Superoxide defect by mutations in Ncf1 gene was subsequently shown to cause arthritis and lupus in mice [5,6], and in humans [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%